2005
DOI: 10.1080/01421590500069710
|View full text |Cite
|
Sign up to set email alerts
|

The learning environment for junior doctor training—what hinders, what helps

Abstract: As part of a larger study on learning outcomes for the first year of postgraduate medical training (already reported), semi-structured interviews with middle grade trainees were used to explore their perceptions of trainee development during this first training year. Data generated focused not only on learning outcomes, but also on important process issues. Dissatisfaction was expressed with formal and informal teaching and learning opportunities. Factors that enhance the learning environment were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 15 publications
2
38
1
1
Order By: Relevance
“…The students' reflections suggest this was successful. Our findings are in keeping with previous research about the LE (Hutchinson 2003;Kendall et al 2005;Pearson and Lucas 2011). What our research adds are key features of a safe LE which students identified that can be deliberately incorporated into a LE.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The students' reflections suggest this was successful. Our findings are in keeping with previous research about the LE (Hutchinson 2003;Kendall et al 2005;Pearson and Lucas 2011). What our research adds are key features of a safe LE which students identified that can be deliberately incorporated into a LE.…”
Section: Discussionsupporting
confidence: 89%
“…Research on learning in the work place emphasises the importance of participation and meaningful interactions (Seabrook 2004b;Kendall et al 2005;Sheehan et al 2005;Egan and Jaye 2009). However concern for the potential harm to both students and patients restricts student participation in clinical situations, limiting students learning about the reasoning and judgment involved in taking responsibility for decisions about patient care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst it is well established that nursing staff generally support junior doctors' training, this is the first report in the UK of nurses guiding trainees specifically in the area of palliative care. 16,17 A pilot study in Australia involving fifth-year medical students working with experienced palliative care nurses produced similar findings, with students reporting increased confidence when confronted with a range of situations relating to death and dying. 18 Palliative care staff also acted as a support network.…”
Section: Discussionmentioning
confidence: 71%
“…Junior doctor dissatisfaction with shift systems is well documented, but it was interesting to find that fear of not meeting staff expectations in remaining foundation programme posts was partly what motivated them to acquire acute skills during the palliative medicine post. 16,25 Trainees commencing their pre-registration year in general practice were similarly concerned about falling behind their peers. 15 When posts were split between oncology and palliative medicine, trainees felt unable to follow patients up and find out what had happened to them.…”
Section: Discussionmentioning
confidence: 99%